Changes in Economic and Financial Synchronisation A Global Factor Analysis - Maravalle, Alessandro (OECD Economics Department Working Papers, 2018)
We estimate dynamic factor models for two sub-samples between 1995 and 2017 for up to 42 advanced and emerging-market economies to investigate changes in the contribution of global and regional factors to fluctuations in real GDP per capita growth, inflation, 10-year government bond yields and equity prices. The combined average contribution of global and regional factors in explaining fluctuations of GDP growth and inflation increased between 1995-2006 and 2007-17. In contrast, for financial variables, the role of country-specific factors strengthened between these two periods. The general findings are robust to alternative specifications of the lag structure, data frequency and the country composition of the largest region. Country-specific factors explain a higher share of variation of financial variables in emerging-market economies compared with advanced economies. For all variables, there is large cross-country heterogeneity regarding the level of contributions of specific factors and their evolution over time